Modeling the thermal environment in an operating room - Teixeira, SFCF (2014)
Comfort is important in everybody's lives, as it is not only a health subject, but also a productive issue. As environmental conditions differ accordingly to the space use, there is a direct influence of this space on human comfort. The Heating Ventilation and Air Conditioning (HVAC) Systems are a crucial way to obtain the expected air quality levels in the interior of buildings and to achieve thermal comfort. These systems ensure air renewal, pressurization, temperature control, and air humidity, being of utmost importance in healthcare facilities. Providing thermal comfort conditions and good air quality, especially in operating rooms, is a difficult task, as the environmental conditions should be suitable for medical staff performance and for patient safety, as well. In the current study, a Computational Fluid Dynamics model was developed and coupled with a thermoregulatory model of the human body to describe the fluid flow, heat transfer and mass transfer between the ventilation air and a human manikin inside an operating room. The CFD simulation solves the heat, mass and momentum conservation equations in the computation domain using a finite volume discretization method, in the ANSYS - environment. The interaction between the body and the environment is determined by the thermoregulatory model, which includes temperature and the moisture diffusion through the cloth fabrics. The combination of the human body and space ventilation models allows evaluating the influence of the main thermal comfort variables on the calculation of comfort index, such as, the PMV.